Longitudinal Associations Between Home Food Environment and Diet Quality in Children - Perez, Jonae Brianne (My University, 2014)
Background: Child and adolescent diets in the United States are high in fat and sodium and low in vegetables, fruits, whole grains, and dairy foods. Parental practices and foods provided in the home greatly influence children's food related behaviors. This impact may change as children progress through adolescence and other factors begin to play a role, such as peers, media, and convenience of food. Objective: This study aimed to investigate longitudinal relationships between parenting around food/eating, foods available in the home, and future child diet quality in younger versus older children. Methods: The National Impact on Kids (NIK) Study was a prospective cohort study with two time points, baseline and 2-year follow-up. Parental surveys were used to collect data on home food environment and 24-hour food recalls were used to collect child dietary intake. Child diet quality indicators include DASH score, fruit and vegetable intake, and high-energy beverage intake. In this secondary data analysis, participants were dichotomized in to two groups: younger (ages 6-8.99) versus older (ages 9-12.5) at study initiation. Hierarchical linear regression models were used to assess the association between initial parenting around food/eating and foods available in the home and future child diet quality indicators. Results: Participants were 50.7% female and predominantly Non-Hispanic White (70.2%). A significant overall change in DASH scores (p=.053), total fruit and vegetable intake (p=.017), and high-energy beverage consumption (p<.001) was seen. There was a significant effect of age on parental permissiveness (p<.001), as well as rules around food (p=.003), however, no significant differences in diet quality were seen between groups. For younger children, initially more parental rules around food was positively related to children's subsequent DASH scores (p=.028); and initial availability of non-nutritious foods in the home was positively related to future high-energy beverage intake (p=.003). For older children, being Non-Hispanic White (p=.023), and initial parental pressure to eat (p=.035), permissiveness (p=.046), and rules around food (p=.019) were positively related to future child DASH scores; initial parental encouragement (p=.009) and permissiveness (p=.015) were positively related to children's future fruit and vegetable intake; and initial home availability of non-nutritious foods (p=.023) and parental restrictiveness (p=.037) was related to higher future high-energy beverage intake. Conclusions: A greater number of longitudinal relationships existed between the home food environment and child diet quality in older as compared to younger children, suggesting that changes in development broadly affect parental influence on child food-related behaviors.
Thesis (Master's)--University of Washington, 2014
Keywords: Children; Diet; Home Food Environment; Nutrition; Parental Practices; Nutrition; nutritional sciences